Relational and Embedded Leadership for Navigating Structural Conflict: A Strategic Model for Adaptive Organizations - Ardiansyah, Rendy; Arenal, Arenal; Priyono, Budi; Pahala, Indra; Handaru, Wahyu (Journal Research of Social Science, Economics, and Management, 2025)
This article develops the Relational and Embedded Strategic Leadership model in response to the limitations of conventional strategic leadership in navigating structural conflicts and adaptive challenges in modern organizations. Through theoretical synthesis and case analysis across sectors including Nokia, Microsoft, Telkom Indonesia, the UK’s NHS, and Finnish & Canada universities, GE, this paper reveals that successful transformation depends more on social relations, distributed leadership roles, and collective sensemaking than on structural control or top-down vision. The proposed model emphasizes dialogic, context-sensitive, and operationally embedded leadership practices. It contributes conceptually to leadership theory by integrating relational and institutional perspectives, while offering practical direction for organizations seeking sustainable change through cross-functional and cross-level participation. Key implications include the need for organizational design that enables distributed leadership, leadership development programs rooted in reflection and empathy, and institutional reforms based on collaboration—particularly in public and higher education sectors.